2022
DOI: 10.3390/membranes12030332
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning of Quaternized Chitosan-Poly(vinyl alcohol) Composite Nanofiber Membrane: Processing Optimization and Antibacterial Efficacy

Abstract: N-(2-hydroxy) propyl-3-trimethylammonium chitosan chloride (HTCC) is a type of quaternary ammonium chitosan derivative with an antibacterial activity superior to the pristine chitosan, but its electrospinnability is limited. In this study, polyvinyl alcohol (PVA) was blended with HTCC to improve the electrospinnability of nanofibers. The electrospinning of PVA–HTCC nanofiber membranes was optimized in terms of structural stability and antimicrobial performance. Based on scanning electron microscopic analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…As mentioned earlier in the Materials and Methods section , the use of guest polymers, easy to spin such as PVA and PEO, has shown great results in terms of fiber formation and homogeneity. 55 , 56 By blending, chitosan becomes easier to electrospin, and nanofibrous mats with homogeneous characteristics can be obtained. For this reason, different concentrations of PVA and PEO were investigated following the various examples reported in the literature, 44 , 45 , 57 and in Table 1 , the final concentrations chosen for our study are reported.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned earlier in the Materials and Methods section , the use of guest polymers, easy to spin such as PVA and PEO, has shown great results in terms of fiber formation and homogeneity. 55 , 56 By blending, chitosan becomes easier to electrospin, and nanofibrous mats with homogeneous characteristics can be obtained. For this reason, different concentrations of PVA and PEO were investigated following the various examples reported in the literature, 44 , 45 , 57 and in Table 1 , the final concentrations chosen for our study are reported.…”
Section: Resultsmentioning
confidence: 99%
“…With the assistance of free amino groups, positively charged polyelectrolyte can be released from chitosan at a pH ranging from 2 to 6; thus, due to their high solubility compared to chitin solutions, chitosan solutions are highly viscous and complicated for electrospinning. 36 Furthermore, the 3-D network formed via strong hydrogen bonding prevents the movement of polymer chains during exposure to the electric field. 37 The TTO-NL solution obtained above was then mixed with PVP/CS solution mentioned above under magnetic stirring at weight ratios of 1:4 (TTO-NL/polyvinyl alcohol/chitosan).…”
Section: Methodsmentioning
confidence: 99%
“…The electrospun nanofiber membranes comprising HTCC/PVA had diameters ranging from 300 to 400 nm [104]. Increasing the electrospinning voltage to 25 kV resulted in a reduction of the fiber diameter to 240 nm [106]. However, increasing the voltage beyond the critical value resulted in the bead formation of HTCC/PVA fibers [106].…”
Section: Overview Of Electrospinning Of Chitosanmentioning
confidence: 99%
“…Increasing the electrospinning voltage to 25 kV resulted in a reduction of the fiber diameter to 240 nm [106]. However, increasing the voltage beyond the critical value resulted in the bead formation of HTCC/PVA fibers [106]. The occurrence of beaded nanofibers at elevated voltages was linked to the reduction in the size of the Taylor cone and the simultaneous increase in jet velocity under consistent flow rates [58].…”
Section: Overview Of Electrospinning Of Chitosanmentioning
confidence: 99%